Monitoring and Prediction of Tropical Cyclones in the Indian Ocean and Climate Change - Mohanty, U.C.; Mohanty, U.C.; Mohapatra, M.; Mohapatra, M.; Singh, O.P.; Singh, O.P.; Bandyopadhyay, B.K.; Bandyopadhyay, B.K.; Rathore, L.S.; Rathore, L.S. (Springer Netherlands : Imprint: Springer, 2014)
This book deals with recent advances in our understanding and prediction of tropical cyclogenesis, intensification and movement as well as landfall processes like heavy rainfall, gale wind and storm surge based on the latest observational and numerical weather prediction (NWP) modeling platforms. It also includes tropical cyclone (TC) management issues like early warning systems, recent high impact TC events, disaster preparedness, assessment of risk and vulnerability including construction, archiving and retrieval of the best tracking and historical data sets, policy decision etc., in view of recent findings on climate change aspects and their impact on TC activity. The chapters are authored by leading experts, both from research and operational environments. This book is relevant to cyclone forecasters and researchers, managers, policy makers, graduate and undergraduate students. It intends to stimulate thinking and hence further research in the field of TCs and climate change, especially over the Indian Ocean region and provides high-quality reference materials for all the users mentioned above for the management of TCs over this region.